Welcome to Westonci.ca, where finding answers to your questions is made simple by our community of experts. Experience the convenience of finding accurate answers to your questions from knowledgeable professionals on our platform. Explore comprehensive solutions to your questions from a wide range of professionals on our user-friendly platform.
Sagot :
To solve the quadratic equation [tex]\(4x^2 - 7x = -3\)[/tex], let's first rearrange it into standard form:
[tex]\[ 4x^2 - 7x + 3 = 0 \][/tex]
Next, we’ll use the quadratic formula to find the roots of the equation [tex]\(ax^2 + bx + c = 0\)[/tex]. The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For the given equation [tex]\(4x^2 - 7x + 3 = 0\)[/tex], the coefficients are:
- [tex]\(a = 4\)[/tex]
- [tex]\(b = -7\)[/tex]
- [tex]\(c = 3\)[/tex]
Now, let's substitute these values into the quadratic formula:
[tex]\[ x = \frac{-(-7) \pm \sqrt{(-7)^2 - 4 \cdot 4 \cdot 3}}{2 \cdot 4} \][/tex]
First, calculate the discriminant ([tex]\(b^2 - 4ac\)[/tex]):
[tex]\[ b^2 - 4ac = (-7)^2 - 4 \cdot 4 \cdot 3 = 49 - 48 = 1 \][/tex]
Now, substitute the discriminant back into the quadratic formula:
[tex]\[ x = \frac{7 \pm \sqrt{1}}{8} \][/tex]
Since [tex]\(\sqrt{1} = 1\)[/tex], we can simplify this further:
[tex]\[ x = \frac{7 \pm 1}{8} \][/tex]
We now have two potential solutions:
[tex]\[ x_1 = \frac{7 + 1}{8} = \frac{8}{8} = 1 \][/tex]
[tex]\[ x_2 = \frac{7 - 1}{8} = \frac{6}{8} = \frac{3}{4} \][/tex]
Thus, the solutions to the equation [tex]\(4x^2 - 7x + 3 = 0\)[/tex] are:
[tex]\[ x = \left\{ \frac{3}{4}, 1 \right\} \][/tex]
So, the correct answer is:
A. [tex]\(x = \left\{ \frac{3}{4}, 1 \right\} \)[/tex]
[tex]\[ 4x^2 - 7x + 3 = 0 \][/tex]
Next, we’ll use the quadratic formula to find the roots of the equation [tex]\(ax^2 + bx + c = 0\)[/tex]. The quadratic formula is given by:
[tex]\[ x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \][/tex]
For the given equation [tex]\(4x^2 - 7x + 3 = 0\)[/tex], the coefficients are:
- [tex]\(a = 4\)[/tex]
- [tex]\(b = -7\)[/tex]
- [tex]\(c = 3\)[/tex]
Now, let's substitute these values into the quadratic formula:
[tex]\[ x = \frac{-(-7) \pm \sqrt{(-7)^2 - 4 \cdot 4 \cdot 3}}{2 \cdot 4} \][/tex]
First, calculate the discriminant ([tex]\(b^2 - 4ac\)[/tex]):
[tex]\[ b^2 - 4ac = (-7)^2 - 4 \cdot 4 \cdot 3 = 49 - 48 = 1 \][/tex]
Now, substitute the discriminant back into the quadratic formula:
[tex]\[ x = \frac{7 \pm \sqrt{1}}{8} \][/tex]
Since [tex]\(\sqrt{1} = 1\)[/tex], we can simplify this further:
[tex]\[ x = \frac{7 \pm 1}{8} \][/tex]
We now have two potential solutions:
[tex]\[ x_1 = \frac{7 + 1}{8} = \frac{8}{8} = 1 \][/tex]
[tex]\[ x_2 = \frac{7 - 1}{8} = \frac{6}{8} = \frac{3}{4} \][/tex]
Thus, the solutions to the equation [tex]\(4x^2 - 7x + 3 = 0\)[/tex] are:
[tex]\[ x = \left\{ \frac{3}{4}, 1 \right\} \][/tex]
So, the correct answer is:
A. [tex]\(x = \left\{ \frac{3}{4}, 1 \right\} \)[/tex]
Your visit means a lot to us. Don't hesitate to return for more reliable answers to any questions you may have. Thank you for choosing our platform. We're dedicated to providing the best answers for all your questions. Visit us again. Get the answers you need at Westonci.ca. Stay informed by returning for our latest expert advice.